Anatomy of hierarchy: Feedforward and feedback pathways in macaque visual cortex. Issue 1 (26th November 2013) - Markov, Nikola T.; Vezoli, Julien; Chameau, Pascal; Falchier, Arnaud; Quilodran, René; Huissoud, Cyril; Lamy, Camille; Misery, Pierre; Giroud, Pascale; Ullman, Shimon; Barone, Pascal; Dehay, Colette; et al.
ABSTRACT The laminar location of the cell bodies and terminals of interareal connections determines the hierarchical structural organization of the cortex and has been intensively studied. However, we still have only a rudimentary understanding of the connectional principles of feedforward (FF) and feedback (FB) pathways. Quantitative analysis of retrograde tracers was used to extend the notion that the laminar distribution of neurons interconnecting visual areas provides an index of hierarchical distance (percentage of supragranular labeled neurons [SLN]). We show that: 1) SLN values constrain models of cortical hierarchy, revealing previously unsuspected areal relations; 2) SLN reflects the operation of a combinatorial distance rule acting differentially on sets of connections between areas; 3) Supragranular layers contain highly segregated bottom‐up and top‐down streams, both of which exhibit point‐to‐point connectivity. This contrasts with the infragranular layers, which contain diffuse bottom‐up and top‐down streams; 4) Cell filling of the parent neurons of FF and FB pathways provides further evidence of compartmentalization; 5) FF pathways have higher weights, cross fewer hierarchical levels, and are less numerous than FB pathways. Taken together, the present results suggest that cortical hierarchies are built from supra‐ and infragranular counterstreams. This compartmentalized dual counterstream organization allows point‐to‐point connectivity in both bottom‐up and top‐down directions. J. Comp. Neurol. 522:225–259, 2014. © 2013 Wiley Periodicals, Inc.